2016
DOI: 10.1016/j.jnoncrysol.2016.06.027
|View full text |Cite
|
Sign up to set email alerts
|

Periodic vs. molecular cluster approaches to resolving glass structure and properties: Anorthite a case study

Abstract: Periodic and molecular cluster models are presented for anorthite (CaAl 2 Si 2 O 8), a cement forming glass with desirable thermal and mechanical properties also tested in dental applications. Both the crystalline and amorphous structures were characterised by ab initio molecular dynamics and found to be in good agreement with experiment. Additional investigations of the elongation and fracture of the glass were also made. The recovery of material properties signaled the failure of the periodic method to gener… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 92 publications
0
17
0
Order By: Relevance
“…The P-P RDF profile of the nanopore is very similar to that of the crystal, which indicates that HAP nanopores remain crystalline. The P-P RDF profile of the HAP surface shows some deviations compared with that of HAP nanopore, suggesting some restructuring of the surface but not to an extend to indicate amorphousization of the surface (Tian et al 2016). This agrees with the previous MD work by de Leeuw, which showed that HAP surfaces maintain its crystalline structure (de Leeuw 2004a, b).…”
Section: Molecular Dynamicsmentioning
confidence: 94%
“…The P-P RDF profile of the nanopore is very similar to that of the crystal, which indicates that HAP nanopores remain crystalline. The P-P RDF profile of the HAP surface shows some deviations compared with that of HAP nanopore, suggesting some restructuring of the surface but not to an extend to indicate amorphousization of the surface (Tian et al 2016). This agrees with the previous MD work by de Leeuw, which showed that HAP surfaces maintain its crystalline structure (de Leeuw 2004a, b).…”
Section: Molecular Dynamicsmentioning
confidence: 94%
“…The PBE method with Goedecker-Teter-Hutter pseudopotentials were employed for core-valence electron interactions, whilst all valence interactions were represented using a double-zeta valence polarized basis set. Additional investigations of the low-energy vibrations were completed with electronic structure calculations using a molecular cluster model 38 and the Gaussian 09 program package, 39 with focus on resolving the interfacial THz modes. Models were geometry-optimised and complemented by analytical frequencies determined at the B3LYP/DGDZVP level of theory.…”
Section: Methodsmentioning
confidence: 99%
“…EDX determined composition for the NiTi alloys was deemed unreliable, firstly due to the unrealistically high carbon content; secondly, EDX only determines superficial composition due to the short penetration depth of electrons as well as the marked discrepancy between EDX-determined surface and bulk compositions [18,40,41]. Thus PGAA, one of the most accurate and efficient non-destructive techniques [42], was applied taking advantage of the deeper penetration depth.…”
Section: Discussionmentioning
confidence: 99%